Early Blockade of TLRs MyD88-Dependent Pathway May Reduce Secondary Spinal Cord Injury in the Rats. (22nd May 2012) - Yao, An-hui; Jia, Li-yun; Zhang, Yu-kai; Ma, Quan-rui; Cheng, Peng; Liu, Ling; Ju, Gong; Kuang, Fang
Abstract : To determine the role of toll-like receptors (TLRs) myeloid differentiation factor 88 (MyD88) dependent pathway in the spinal cord secondary injury, compression injury was made at T8 segment of the spinal cord in adult male Sprague-Dawley rats. Shown by RT-PCR, TLR4 mRNA in the spinal cord was quickly elevated after compression injury. Intramedullary injection of MyD88 inhibitory peptide (MIP) resulted in significant improvement in locomotor function recovery at various time points after surgery. Meanwhile, injury area, p38 phosphorylation, and proinflammation cytokines in the injured spinal cord were significantly reduced in MIP-treated animals, compared with control peptide (CP) group. These data suggest that TLRs MyD88-dependent pathway may play an important role in the development of secondary spinal cord injury, and inhibition of this pathway at early time after primary injury could effectively protect cells from inflammation and apoptosis and therefore improve the functional recovery.